The National Character Building in “Pudarnya Pesona Cleopatra” - Muhammad Zainurroziqin; Mutmainnah Mustofa; Miftahur Rohmah; Erfan Erfendi (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
The study is aimed to analyse national character building in Novel entitled “Pudarnya Pesona Cleopatra. The researcher referred to the list of character building according to Doni Koesoema 2007. The research applied descriptive qualitative research method. The method of gathering data is the Documentation method. The researcher intended to describe the National Character Building based on the utterances and behaviour of the main characters in the Novel. The data analysis is a significant step in a part of this research, because it aims examining the data collection’s validity and reliability. In analysing the data, the procedures are 1) the researcher selected the Novel. 2) The researcher read the Novel. 3) The researcher tried to find the National Character Building from “Pudarnya Pesona Cleopatra”. 4) The researcher analysed the data. 5) The researcher drew the conclusion based on the data analysis. Based on the finding of this research, the writer found religious, responsible, hard-working, curious, respectful, inclusive and communicative, peace-loving, and compassion in the novel “Pudarnya Pesona Cleopatra”. There are 7 religious, 2 responsible, 3 hard-working, 1 curious, 2 respectful, 2 inclusive and communicative, 7 peace-loving, and 2 compassion in the novel.